Growth improvement of wheat (Triticum aestivum) and zinc biofortification using potent zinc-solubilizing bacteria - Ali, Murad; Ahmed, Iftikhar; Tariq, Hamza; Abbas, Saira; Zia, Munir Hussain; Mumtaz, Amer; Sharif, Muhammad (Frontiers in Plant Science, 2023)
Zinc (Zn) is an indispensable element for proper plant growth. A sizeable proportion of the inorganic Zn applied to soil undergoes a transformation into an insoluble form. Zinc solubilizing bacteria (ZSB) have the potential to transform insoluble Zn to plant accessible forms and are thus, promising alternatives for Zn supplementation. The current research was aimed at investigating the Zn solubilization potential of indigenous bacterial strains and to evaluate their impact on wheat growth and Zn biofortification. A total of sixty-nine strains were assessed for their Zn solubilizing ability against two insoluble Zn sources (ZnO and ZnCO3). The solubilization index and solubilization efficiency were measured qualitatively and further tested quantitatively for Zn and phosphorus (P) solubility. Results showed that broth culture pH was negatively correlated with Zn solubilization i.e., ZnO (r2=0.88) and ZnCO3 (r2=0.96). Ten novel promising strains were selected for further experimentation on wheat crop based on plant growth promoting rhizobacteria (PGPR) traits. A control experiment was also conducted to determine the highest critical Zn level from ZnO to wheat growth using different Zn levels (0.1, 0.05, 0.01, 0.005 and 0.001 % Zn) against two wheat varieties (Wadaan-17 and Zincol-16) in sand culture and 50 mg kg-1 of Zn was identified as the highest critical level for wheat growth. Using this critical level, the selected ZSB strains were inoculated alone and in consortium to seed of wheat, with and without the use of ZnO, in sand culture. The ZSB inoculation in consortium without ZnO improved shoot length (14 %), shoot fresh weight (34 %), shoot dry weight (37 %); and with ZnO root length (116 %), root fresh weight (435 %), root dry weight (435 %) and Zn content in shoot (1177 %) as compared to control. Wadaan-17 performed better on growth attributes, while Zincol-16 had 5% more shoot Zn concentration. The present study concluded that selected bacterial strains showed the potential to act as ZSB and are highly efficient bio-inoculants to combat Zn deficiency. The study further concluded that 50 mg kg-1 Zn from ZnO had no negative impact on wheat growth, however higher concentrations hampered wheat growth.